Dampak Platform Media Sosial TikTok terhadap Perilaku Siswa Kelas III SDN Cibiru 06 : Impact of the TikTok Social Media Platform on the Behavior of Class III Students at SDN Cibiru 06 - Ageng Saepudin Kanda S; Tiara Meriska, Erika (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the development of science and technology that has occurred in this era, various social media platforms have emerged which are often useful for society as a means of communication with other people, even though they are separated by great distances. However, the emergence of various social media platforms has certainly had both positive and negative impacts. Especially regarding the behavior of children of elementary school age who are considered still vulnerable to the influence of social media. The use of qualitative methods with interview data collection techniques with parents, students and class III teachers at SDN Cibiru 06 as well as literature studies from various journal references and scientific articles in this research resulted in this article. This research obtained results that TikTok social media for class III students at SDN Cibiru 06 tends to have a negative influence on their behavior. This is due to a lack of parental supervision when children are playing with gadgets, especially when playing on social media TikTok because parents are too busy with work. However, it cannot be denied that TiTok social media is capable of having a positive influence, especially when it can be used with tools and facilities that support the implementation of learning activities.